cDNA Microarray Image Analysis - Tozduman, Ersin; Albayrak, Songuel (IEEE, 2009)
cDNA microarray image analysis has grown very important these days because of the growing field which it's part of: microarray erpression analysis. In this work we propose a new cDNA microarray image analysis system. A cDNA microarray analysis system consists of three main parts which are Gridding, Segmentation and Information Extraction, respectively. In gridding stage we propose a new automated gridding technique which is based on mathematical morphology. For segmentation we propose two different algorithm which are based on K-Means clustering and Fuzzy C-Means clustering respectively. On the final stage, information extraction, our proposed system uses a classical approach which calculates background values locally. The proposed system has open parts in the way of developement and is still being worked on.
Keywords: Engineering